2003
DOI: 10.3171/spi.2003.99.3.0291
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proteoglycan and type II collagen synthesis of disc nucleus cells by nicotine

Abstract: Object. Systemic nicotine has been hypothesized to cause degeneration of the intervertebral disc which in turn decreases vascular supply to the disc through a cholinergic receptor—mediated process. Another possible mechanism may be through direct regulatory effects on disc cells. In this study, the authors tested the hypothesis that nicotine adversely affects nucleus pulposus cells by directly inhibiting proteoglycan synthesis and gene expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 37 publications
0
13
1
1
Order By: Relevance
“…We have previously shown that nicotine could cause intervertebral disc degeneration by reducing the blood fl ow to intervertebral discs [4] . On the other hand, Kim et al [3] showed that nicotine, by directly affecting nucleus pulposus (NP) cells in the intervertebral discs, is involved in intervertebral disc degeneration by inducing the synthesis of sulfated glycosaminoglycans, and downregulating type II collagen and Sox9 mRNAs via inhibition of the effect of bone morphogenic protein-2. However, cigarettes contain a variety of constituents, and at least two or more factors seem to be involved in intervertebral disc degeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that nicotine could cause intervertebral disc degeneration by reducing the blood fl ow to intervertebral discs [4] . On the other hand, Kim et al [3] showed that nicotine, by directly affecting nucleus pulposus (NP) cells in the intervertebral discs, is involved in intervertebral disc degeneration by inducing the synthesis of sulfated glycosaminoglycans, and downregulating type II collagen and Sox9 mRNAs via inhibition of the effect of bone morphogenic protein-2. However, cigarettes contain a variety of constituents, and at least two or more factors seem to be involved in intervertebral disc degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vivo experiments have demonstrated that exposure to nicotine, a major chemical constituent of cigarettes, induces intervertebral disc degeneration [2][3][4][5] . Exposure to nicotine, through systemic effects related to cholinergic nicotinic receptors, leads to increased blood pressure, vasoconstriction and vascular resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It had been demonstrated that H 2 O 2 may stimulate DNA oxidative damage in the NP cells of rats (24) and in the present research a DNA oxidative damage model was established by applying different concentrations of H 2 O 2 (0.05, 0.1 and 0.2 mM/l). COL2 expression was used to monitor the degeneration of NP cells, following a previously described protocol (25). The expression of COL2 decreased as increasing concentrations of H 2 O 2 were used, whereas the expression of TSHZ3 increased in an H 2 O 2 concentration-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Durch Zigarettenrauch verursachte Auswirkungen auf die Bandscheiben wurden von Holm und Nachemson erforscht, welche insbesondere vaskuläre Effekte und erhöhte Kohlenstoffmonoxidkonzentrationen für die Bandscheibendegeneration verantwortlich machen [8]. Während niedrige (100 µg/mL [27]) und sehr hohe Nikotindosen von etwa 8000-50 000 µg/mL [17] den Metabolismus von Zellen des Nucleus pulposus sowie die Produktion von Glycosaminoglykanen und Kollagen in vitro hemmen, werden diese durch mittelhohe Dosen (etwa 4000 µg/mL) vorübergehend stimuliert, bis sie nach 7 Tagen ebenfalls abnehmen [17]. Die Serumkonzentration von Nikotin bei starken Rauchern (20-30 Zigaretten pro Tag) beträgt etwa 0,01-0,07 µg/ml [28] und liegt somit z. T. deutlich unter den applizierten Konzentrationen der obigen In-vitro-Versuche.…”
Section: Rauchen Fördert Bandscheibenschädenunclassified